Pendidikan Tri Hita Karana Dalam Prosesi Nunas Babungah Petapakan Ida Bhatara Ratu Gede Dan Ida Bhatara Ratu Lingsir Desa Adat Tegal Suci Desa Sebatu Kabupaten Gianyar - Degus Jaya, I Wayan; Wisarja, I Ketut (Jayapangus Press, 2024)
Traditional villages regulate community belief patterns, one of which is the community belief system, especially community rituals. This is included in the visualization of the belief system, namely God himself through Barong and Rangda. Especially the Tegal Suci Traditional Village which has sungsungan Barong and In color complete with mask escort. This research aims to reveal more deeply the value of education Three hit karana contained in the process Nunas Pabungah. This research uses a qualitative descriptive research method with data collection techniques of observation, interviews and documentation. The results of this research show that the Tegal Suci Traditional Village has a very interesting procession which is called the process Nunas Pabungah once every 6 months. Procession Nunas Pabungah held at the subah pamuus temple. The connection between the temple and the Tegal Suci Traditional Village is due to springs and clothing ida bhatara, a pair of tumbak and a set of gambelan. The essence of the story in the play tells the story of the Garuda's ability to protect the holy Tegal community of nature. As for the value of education Three hit karana covers Pahrayangan belief in the power of God or special ida bhatara big queen who is believed to be able to protect his companions and ida bhatara the powerful queen of Pamuus Temple who is believed to control the prosperity of food, People the bonding of banjar manners which then gave birth to a process of mutual cooperation in the effort of ngayah together nyungsung and holding rituals Nunas Pabungah, Palemahan protecting the environment or natural resources, the presence of the Garuda's bisama as a warning to the people of Tegal Suci not to forget to protect water sources and always return the produce of the land in the form of upakara.